The law of loyalty - Smith, Lionel D. (Oxford University Press, 2023)
'The Law of Loyalty' elucidates common legal principles underlying the use of juridical powers. It addresses both public law and private law, and examines both the common law and the civil law. It provides a theory of how Western law regulates the situations in which we hold legal powers, not for ourselves, but for and on behalf of others.